2023
DOI: 10.3390/ijms24043375
|View full text |Cite
|
Sign up to set email alerts
|

Research Status and Prospect of Non-Viral Vectors Based on siRNA: A Review

Abstract: Gene therapy has attracted much attention because of its unique mechanism of action, non-toxicity, and good tolerance, which can kill cancer cells without damaging healthy tissues. siRNA-based gene therapy can downregulate, enhance, or correct gene expression by introducing some nucleic acid into patient tissues. Routine treatment of hemophilia requires frequent intravenous injections of missing clotting protein. The high cost of combined therapy causes most patients to lack the best treatment resources. siRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 215 publications
0
9
0
Order By: Relevance
“…Nevertheless of competent gene-silencing effects, cancer treatment using TpRNAs is limited due to their short body circulation time, targeting inability, poor target accumulation ability, instability, low cellular uptake, and etc [17,18]. To overcome the above hurdles, the following approaches are used in delivering TpRNAs-viral vectors and non-viral vectors [19,20]. Viral vectors are classified into (i) genedelivery vehicles (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless of competent gene-silencing effects, cancer treatment using TpRNAs is limited due to their short body circulation time, targeting inability, poor target accumulation ability, instability, low cellular uptake, and etc [17,18]. To overcome the above hurdles, the following approaches are used in delivering TpRNAs-viral vectors and non-viral vectors [19,20]. Viral vectors are classified into (i) genedelivery vehicles (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, viral vectors are the most commonly used in clinical trials of gene therapy drugs [1]. However, along with the high delivery efficacy due to the life cycle of viruses, these vectors are immunogenic, and their use can lead to undesirable toxic effects for patients [2,3]. Liposomes, polycations, peptides, and inorganic compounds are examples of non-viral carriers.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that although the viral vector has high transfection efficiency, its application is greatly limited due to the potential security risks, such as the occurrence of leukemia induced by some retroviruses, and the limited capacity of the viral vector 35 . In contrast, nonviral vectors have the advantages of low cost, simple preparation, easy mass production, high safety, and unlimited length of exogenous genes 36 . Plasmid vector is an attractive in vivo transfection vector in animals that can be injected directly into specific tissues and can achieve effective higher levels of gene expression in vivo.…”
Section: Introductionmentioning
confidence: 99%